Plug-in SonarQube para validar la calidad en los modelos de procesos de negocio en notación BPMN. (2016)
In a company, being able to reach organizational goals is the most important aspect of each of them, because of this importance, the one that is clear to all its stakeholders is of vital importance. Therefore, the quality of the business process models (models that indicate how to reach those goals) is an essential aspect for the development and technological support of any company. Starting from the hypothesis that the quality of business process models can be analyzed, a plug-in for the SonarQube tool was created, which allows validating the quality of these models. This paper shows some guidelines and quality metrics for the evaluation of these business processes. This evaluation is done after making the model of the process in the Bonita Studio tool, then, using the SonarQube code evaluation tool together with the plug-in created in this work (which already contains the metrics), a state of The technical debt of the model, obtaining the quality of each one of these models with respect to the established metrics.